Evaluación de riesgo ergonómico a los Drs. Odontólogos del Distrito 12d06 Buena Fe-Valencia - Ortiz Chapín, Duber Elías (2017)
The well-being of the health professional occupies a very important place at present, therefore, the greater level of information that is obtained by the investigations on the occupational health problems will contribute especially to the promotion and prevention of the diseases and to guarantee a better standard of living for the professional. The importance of the work lies in knowing if there is any application of ergonomics in the daily work of dentists, to relate the musculoskeletal complications of professionals in their activity. The beneficiaries of the result of this work will be the Dentists in general and specifically those of the district 12D06 Buena Fe-Valencia, who will benefit because the researcher will make a proposal to the identified problem, managing to solve this pressing situation. The impact of investigative work is based on the fact that in our country and in the province of Los Rios, there are few studies on the subject, which prevents the establishment of institutional actions for the prevention, diagnosis and treatment of these pathologies.